Mental well-being and mindfulness - Woolley, Katie; Wheatcroft, Ryan (London Wayland, 2019)
Mental health is as important as physical health. It increases self-confidence and self-esteem as well as helping you to cope with any stressful stituation. Lean how to tackle bullying, worry and anxiety by looking after your mental health, from finding time to have fun with friends, to eating well, exercising or trying some easy mindfulness techniques
Education
1 2 13 22 23
Keywords: Mental health -- Juvenile literature; Mindfulness (Psychology) -- Juvenile literature